EFFECT OF FEEDING RICE IMPURITIES WITH OR WITHOUT ACETIC ACID ON PRODUCTIVE PERFORMANCE OF AWASSI LAMBS - A., Jaafar K.; Al-Ani, J. A. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of this experiment was to study the effect of replacing treated and untreated rice impurities with urea, with or without acetic acid on the digestibility and performance of Awassi lambs. Twenty-four Awassi male lambs, aged 3-4 months with an initial weight 25.08 ± 0.64kg were divided into six treatments in a 2×3 factorial experiment/ Completely Randomized Design. Experiment period was 56 days, 14/3/2022 to 9/5/2022, preceded by 10 days as an adaptation period. Individual feeding was conducted. All animals fed on three levels of rice impurities treated with urea (0, 50,100%) without acetic acid (T1, T2, T3) and with 1% acetic acid (T4, T5, T6) respectively. The results showed a highly increase (P